A MINING TOWN FROM TANZIMAT TO REPUBLIC: BALYA (1839–1923) - - (Fırat University, 2019)
In this study, socio-economic and demographic transformation of Balya during the period between “Tanzimat” and “Cumhuriyet” is going to analyzed within the concept of mining activities. Especially the effects of mining activities on this transformation are emphasized upon. Moreover, transform and rise of Balya from “Kocagumus” village into a town and later into a city through mining activities are going to be examined in historical perspective. Finally, miners’ strikes are going to be touched upon.